Comparação clínica e de mediadores inflamatórios no tratamento empírico da conjuntivite aguda - Santiago, Luiz Alfredo (2022)
Conjunctivitis is an irritation or inflammation of the conjunctiva, which covers the white part of the eye. It can be caused by allergies, bacterial or viral infection. Conjunctivitis can be contagious, being transmitted through contact with the infected person's eye secretions. This study aimed to evaluate the effects of prednisolone versus diclofenac sodium with both ciprofloxacin and artificial tears on symptoms and signs of acute viral conjunctivitis. The study included 37 patients diagnosed with acute conjunctivitis and were divided into three groups: group A received 1% prednisolone acetate + ciprofloxacin (0.3%); group B received diclofenac sodium (0.1%) + ciprofloxacin (0.3%) and group C received artificial tears + ciprofloxacin (0.3%) %). Patients received medication 6/6 hours daily. Signs and symptoms such as tearing, burning, photophobia, conjunctival hyperemia, discharge, conjunctival reaction, pain and foreign body sensation, itching, were scored at the beginning of the study and on the first, third, fifth and seventh days and at the end of treatment using a standardized questionnaire template and slit lamp anterior segment examination. All three groups demonstrated an improvement in the signs and symptoms of conjunctivitis at their follow-up visits. There was no significant difference in symptom and sign scores between groups A and B and B and C at study visits (p>0.05). However, the comparison between groups A and C showed a clinical trend (p = 0.05) in the third assessment, suggesting a better clinical action with the use of corticosteroids. Prednisolone acetate was not superior to the use of sodium diclofenac or artificial tears in alleviating the signs and symptoms of viral conjunctivitis.